Mechanical Thrombectomy for Stroke After Cardiac Surgery. Issue 8 (10th June 2016) - Madeira, Márcio; Martins, Catarina; Koukoulis, Giovanna; Marques, Marta; Reis, João; Abecassis, Miguel
Abstract: Stroke after cardiac surgery remains a devastating complication and its treatment options are limited. Systemic fibrinolysis is a relative contraindication, because it raises the risk of systemic hemorrhage. Endovascular therapy, mechanical thrombectomy, and intra‐arterial fibrinolysis have emerged as safer options. We present three patients who developed strokes following cardiac surgery who underwent successful mechanical thrombectomy and review the literature on this subject. doi: 10.1111/jocs.12776 (J Card Surg 2016;31:517–520)